Landscape of discontent : urban sustainability in immigrant Paris. - Newman, Andrew (A quadrant book., 2015)
On a rainy day in May 2007, the mayor of Paris inaugurated the Jardins d'Eole, a park whose completion was hailed internationally as an exemplar of sustainable urbanism. The park was the result of a hard-fought, decade-long protest movement in a low-income Maghrebi and African immigrant district starved for infrastructure, but the Mayor's vision of urban sustainability was met with jeers. Drawing extensively from immersive, firsthand ethnographic research with northeast Paris residents, as well as an analysis of green architecture and urban design, Andrew Newman argues that environmental politics must be separated from the construct of urban sustainability, which has been appropriated by forces of redevelopment and gentrification in Paris and beyond. France's turbulent political environment also provides Newman with powerful new insights into the ways in which multiethnic coalitions can emerge--even amid overt racism and Islamophobia--in the struggle for more just cities and more inclusive societies. A tale of multidimensional political efforts, Landscape of Discontent cuts through the rhetoric of green cities to reveal the promise that environmentalism holds for urban communities anywhere -- Présentation de l'éditeur.